Dead lake - Coates, Darcy (Poisoned Pen Press, 2020)
"Sam is excited to spend a week at her uncle's remote lakeside cabin. It's a chance for her to focus on her art without distractions: no neighbors, no phone, and a small radio as her only contact with the outside world. But there's something deeply unnatural lingering in the lake. News reports talk about disappearances on a nearby hiking trail. The car won't start. And Sam starts to believe she's being stalked when she catches glimpses of a tall, strange man standing at the end of her dock, staring intently into the swirling waters below. Stranded, alone, afraid, Sam may have become the prey in a hunter's deadliest game ..."--